Mineralogical and Textural Characterization of Various Shear Types in the Siilinjärvi Apatite Mine, central Finland - Rahkola, Kalle (fi=Turun yliopisto|en=University of Turku|, 2017)
The Siilinjärvi carbonatite complex in central Finland is mined for apatite to produce phosphoric acid and fertilisers. The mining started in 1979 from the Särkijärvi open pit, which is presently the biggest open pit in Finland. The use of the sheared ore-bearing rock material has increased in the beneficiation plant, and it will further increase in the future. The aim of this study is to mineralogically characterise the various shear types in the Siilinjärvi apatite mine. At the mine, the ore is categorised into four different classes depending on their grinding properties. The different ore types were investigated with mineral liberation analyser (MLA), electron probe microanalyser (EPMA) and polarised light microscope. Totally the study comprises 20 samples, and they include all the four ore types of Siilinjärvi. The deformation of the Siilinjärvi ore does not have a distinct influence on the abundances of phlogopite and apatite, but it contributes to the proportions of different carbonate and amphibole minerals and changes the mineral grain sizes and textures. Deformation intensity can be tentatively evaluated from the mineral textures. Deformation introduces new minerals to the rocks, most importantly talc, which is problematic from the process control point of view. Deformation does not have a distinct influence on the chemical composition of apatite. Some minor modifications can be seen in the carbonate minerals and phlogopite, but the changes in the amphiboles are quite prominent.